2020
DOI: 10.1002/anie.202010205
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ethylene on Efficiency and Stereocontrol in Olefin Metathesis: When to Add It, When to Remove It, and When to Avoid It

Abstract: Ethylene is the byproduct of olefin metathesis reactions that involve one or more terminal alkenes. Its volatility is one reason why many cross‐metathesis or ring‐closing metathesis processes, which are reversible transformations, are efficient. However, because ethylene can be converted to a methylidene complex, which is a highly reactive but relatively unstable species, its concentration can impact olefin metathesis in other ways. In some cases, introducing excess ethylene can increase reaction rate owing to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 167 publications
3
39
0
Order By: Relevance
“…Both syn ‐ and anti ‐alkylidene signals of 1 d and the new alkylidene slowly disappeared over a few hours, suggesting decomposition of the active species. Catalytic reactions were conducted in open vials to allow escape of ethylene gas from the reaction mixture [34] . Reactions in closed vials exhibited a lower conversion of 2 to 3 in all cases (entries 1–5, Table 1), confirming the catalyst's limited stability in the presence of ethylene.…”
Section: Methodsmentioning
confidence: 88%
“…Both syn ‐ and anti ‐alkylidene signals of 1 d and the new alkylidene slowly disappeared over a few hours, suggesting decomposition of the active species. Catalytic reactions were conducted in open vials to allow escape of ethylene gas from the reaction mixture [34] . Reactions in closed vials exhibited a lower conversion of 2 to 3 in all cases (entries 1–5, Table 1), confirming the catalyst's limited stability in the presence of ethylene.…”
Section: Methodsmentioning
confidence: 88%
“…It is however noteworthy that in few cases the presence of ethylene can be used to accelerate the metathesis of internal olens. 191 This is particularly pronounced for the tungsten oxo cationic catalysts that contain a bulky NHC stabilizing ligand, where ethylene is thought to help interconversion of the metal centre between resting and active states. 126 Moreover, detailed NMR studies have revealed the parallel between the NMR spectroscopic signatures of molecular and silica-supported TBP and SP metallacyclobutanes, pointing in particular to the observation of very deshielded a-carbon and shielded b-carbon in TBP structures.…”
Section: Conclusion Generalizations and Perspectivesmentioning
confidence: 99%
“…It is however noteworthy that in few cases the presence of ethylene can be used to accelerate the metathesis of internal olefins. 191 This is particularly pronounced for the tungsten oxo cationic catalysts that contain a bulky NHC stabilizing ligand, where ethylene is thought to help interconversion of the metal centre between resting and active states. 126 …”
Section: Conclusion Generalizations and Perspectivesmentioning
confidence: 99%
“…Interestingly, the best results for RCM were obtained when peptide solutions of 120 c and 120 d were added to the refluxing catalyst solution under the N 2 stream to give the product 121 c and 121 d in 51 and 73 % respectively. It was also found that the ethylene, a byproduct of olefin metathesis, can impact the rate of RCM negatively, [62] thus its removal with the help of N 2 stream played a notable role in the yield of RCM. The yield of 121 c was increased from < 5 % to 34 % by bubbling nitrogen gas through the reaction.…”
Section: Developments In Imcr/rcm Merging Strategymentioning
confidence: 99%